Sovereign credit ratings - Ann-Charlotte Eliasson (Deutsche Bank Research, 2002)
This paper describes sovereign credit ratings in emerging markets both for a specific year and over time, using quantitative explanatory variables. It turns out that rating adjustments have been worse than what economic fundamentals justify for some countries and also more frequently altered, questioning the long-term properties of sovereign ratings. The results support the view that rating changes during the Asian crisis have been procyclical rather than counter-cyclical. Omitted variables, such as soundness of banking sector, social and political factors, can be one reason for this misalignment but cannot explain all.
Keywords: C23; C51; G23; 330; Dynamic model; panel data; sovereign credit ratings; emerging markets; Länderrisiko; Aufstrebende Märkte; Schätzung; Welt